2000
DOI: 10.1017/s0952523800174012
|View full text |Cite
|
Sign up to set email alerts
|

Striate cortex increases contrast gain of macaque LGN neurons

Abstract: Recurrent projections comprise a universal feature of cerebral organization. Here, we show that the corticofugal projections from the striate cortex (VI) to the lateral geniculate nucleus (LGN) robustly and multiplicatively enhance the responses of parvocellular neurons, stimulated by gratings restricted to the classical receptive field and modulated in luminance, by over two-fold in a contrast-independent manner at all but the lowest contrasts. In the equiluminant plane, wherein stimuli are modulated in chrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
90
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(103 citation statements)
references
References 56 publications
(73 reference statements)
11
90
2
Order By: Relevance
“…Indeed, numerous studies using a variety of experimental techniques to manipulate CG feedback have documented changes in the magnitude of LGN responses (7)(8)(9)(10)(11)(12)(13)(14). Our results are consistent with some, but not all, of these observations.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Indeed, numerous studies using a variety of experimental techniques to manipulate CG feedback have documented changes in the magnitude of LGN responses (7)(8)(9)(10)(11)(12)(13)(14). Our results are consistent with some, but not all, of these observations.…”
Section: Discussionsupporting
confidence: 90%
“…Some have proposed that CG feedback modulates the gain (7)(8)(9)(10)(11)(12)(13)(14) and/or the spatiotemporal properties of LGN neurons (15)(16)(17). Others have proposed that corticothalamic feedback controls whether thalamic neurons are in a state of net excitation or inhibition (8,12), depending upon oscillatory activity in corticothalamic networks (18).…”
mentioning
confidence: 99%
“…A mixed ANOVA revealed that extraclassical stimuli of either orientation were not any more effective in reducing the R max ratio in on-center cells (Ϫ0.27 6 0.04) than they were in off-center cells (0.23 60.04). Przybyszewski et al (2000) found that the gain of parvocellular and magnocellular neurons is increased by feedback from the striate cortex in the macaque. Unlike the stimulus paradigm used here, in their experiments they stimulated the classical receptive field but did not explore the effects of extraclassical stimuli.…”
Section: Extraclassical Inhibition In Neurons From Different Lamina Omentioning
confidence: 98%
“…We confirm this finding in magnocellular neurons in the marmoset, and extend it by showing results that suggest that the excitatory influence of the cortex in the LGN is blocked by stimulating beyond the classical receptive field. We used only stimuli that were modulated in luminance, and it may be that chromatic contrast is more effective for activating the feedback projection from V1 to parvocellular neurons (Przybyszewski et al, 2000). Parvocellular neurons were also less susceptible than magnocellular neurons to inhibition from beyond the classical receptive field.…”
Section: Cortico-geniculate Excitation and Extraclassical Inhibition mentioning
confidence: 99%
See 1 more Smart Citation